System of education in Kazakhstan and Canada considering features of bilingualism - Pecherskikh, T.F.; Maksimenkova, T.N. (KSU publ., 2015)
The article studies the phenomenon "bilingualism" in educational space, universal tendencies of development of bilingual training and feature of education systems in Kazakhstan and Canada.
Keywords: bilingual education; bilingualism; the native language; a foreign language; training in higher education institution